2012
DOI: 10.1002/stem.1104
|View full text |Cite
|
Sign up to set email alerts
|

Human-Induced Pluripotent Stem Cells form Functional Neurons and Improve Recovery After Grafting in Stroke-Damaged Brain

Abstract: Reprogramming of adult human somatic cells to induced pluripotent stem cells (iPSCs) is a novel approach to produce patient-specific cells for autologous transplantation. Whether such cells survive long-term, differentiate to functional neurons, and induce recovery in the strokeinjured brain are unclear. We have transplanted longterm self-renewing neuroepithelial-like stem cells, generated from adult human fibroblast-derived iPSCs, into the stroke-damaged mouse and rat striatum or cortex. Recovery of forepaw m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
289
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(303 citation statements)
references
References 47 publications
(60 reference statements)
7
289
0
Order By: Relevance
“…Immunohistochemical and immunofluorescence staining verified that iPSCs and NSCs migrated to the area close to the ischemic area, where they expressed the mature neuronal marker NeuN, mature astrocyte marker GFAP, and endothelial cell marker vWF. These findings corroborate other previous studies (on NSCs or iPSCs used individually), which demonstrated that stem cells survived, migrated, and differentiated into mature neurons (26) or angiogenic cells (19) and improved functional recovery via promoting vascular endothelial growth factor expression and enhancing endogenous plasticity in the injured brain (27). Transplantation of iPSCs could improve the motor function, reduce infarct size, attenuate inflammation cytokines, and mediate neuroprotection after ischemic stroke (10,28).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Immunohistochemical and immunofluorescence staining verified that iPSCs and NSCs migrated to the area close to the ischemic area, where they expressed the mature neuronal marker NeuN, mature astrocyte marker GFAP, and endothelial cell marker vWF. These findings corroborate other previous studies (on NSCs or iPSCs used individually), which demonstrated that stem cells survived, migrated, and differentiated into mature neurons (26) or angiogenic cells (19) and improved functional recovery via promoting vascular endothelial growth factor expression and enhancing endogenous plasticity in the injured brain (27). Transplantation of iPSCs could improve the motor function, reduce infarct size, attenuate inflammation cytokines, and mediate neuroprotection after ischemic stroke (10,28).…”
Section: Discussionsupporting
confidence: 90%
“…NSCs had a significantly better effect within the first 2 wk, whereas iPSCs had a more steady effect over 2 wk. This observation was not entirely unexpected as it has been found that iPSCs could form functional neurons and improve the neurologic function up to 4-12 wk (19,27), whereas NSCs have significant therapeutic effects at 2 wk after transplantation (30,31), yet the prolonged effect in vivo has not been universally demonstrated. We suppose that cerebral ischemia appeared to activate the neurogenesis program: transplanted NSCs may act as a functional cell type in an earlier time course after transplantation, whereas iPSCs might differentiate into a more specific functional cell type before promoting the recovery of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 92%
“…Mixed results have been obtained when either rodent or human iPSC-derived progenitor cells have been transplanted into stroke-damaged mouse or rat brains. Results ranged from tumor development and the absence of any effects on behavior to significant recovery of function, controllable cell proliferation, and formation of electrophysiologically active synaptic connections (25)(26)(27)(28). Among the reasons for variability are the absence of standard protocols for cell preparation and for modeling stroke and testing treatment outcomes.…”
Section: Testing Ipscs In Animal Disease Modelsmentioning
confidence: 99%
“…Recent studies have showed that grafted human iPSC cells can generate functional neurons that can send projections and receive synaptic input from neighbouring neurons, which lead to improvement of motor function even in aged animals [10,25]. NSCs mechanisms of action seems to be much complex than simply neuroreplacement.…”
Section: Neural Progenitor Cell Therapy In the Post-acute Phase Of Stmentioning
confidence: 99%